2023
DOI: 10.1186/s12893-023-01945-4
|View full text |Cite
|
Sign up to set email alerts
|

Value of cytopathology in the diagnosis of adenoid cystic carcinoma and an analysis of misdiagnoses

Abstract: Background The diagnosis of adenoid cystic carcinoma (ACC) by cytopathology can be challenging. This study was aimed at testing the effectiveness of this technique and at assessing possible differences in the coincidence rate of fine-needle aspiration cytology(FNAC) and brush exfoliation. Methods The pathology database of Southwest Medical University( Luzhou, China) was searched for patients who had undergone surgery or biopsy for ACC between Janua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…Diagnostic accuracy, specificity, and sensitivity were 90.6%, 94.3%, and 73.6%, respectively. Consistent with our results were accuracy, specificity, and sensitivity in the studies of Wan Y, Akhavan-Moghadam J, and Alwagdani A [ 3 - 5 ]. Other studies showed different accuracy, specificity, and sensitivity results.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Diagnostic accuracy, specificity, and sensitivity were 90.6%, 94.3%, and 73.6%, respectively. Consistent with our results were accuracy, specificity, and sensitivity in the studies of Wan Y, Akhavan-Moghadam J, and Alwagdani A [ 3 - 5 ]. Other studies showed different accuracy, specificity, and sensitivity results.…”
Section: Discussionsupporting
confidence: 91%
“…It has been proposed to report a low specificity percentage for malignant transformation [ 2 - 6 ]. In a cytopathologic study to diagnose adenoid cystic carcinoma of the parotid gland, the final biopsy revealed that FNA reported an accuracy of 90% [ 3 ]. Akhavan-Moghadam et al studied FNA results for head and neck masses and reported accuracy, sensitivity, and specificity to be 92.3%, 95%, and 85%, respectively [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…ADCC accounts for 14.5% of all salivary gland tumors and 41% of malignant tumors of the large and small salivary glands. [ 1 ] Fine-needle aspiration has been utilized for the evaluation of salivary gland lesions with high sensitivity and specificity. [ 2 ] This report highlights cytohistomorphological correlation in a case of metastatic high-grade transformation (HGT) of ADCC in a 52-year-old male patient presenting with cervical lymphadenopathy and an intraoral mass.…”
Section: Introductionmentioning
confidence: 99%